Correlation between mindfulness engagement and self-reported academic performance in medical students - Mubeen Safdar; Tayyab Sajjad; Ammar Asif; Farooq Ahmed; Noor-i-Kiran Naeem (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Mindfulness practices are recognized as effective strategies for coping with stress in medical education. This study aims to determine the correlation between mindfulness engagement and self-reported academic performance in medical studentsMETHODOLOGY: An analytical cross-sectional study was conducted from October 2023 to March 2024, involving 90 undergraduate medical students. Data were collected online using Google Forms and analyzed in Google Sheets. Students' self-reported academic achievement was then correlated with mindfulness practices. A p-value of less than 0.05 was considered significant.RESULTS: The mean age of participants was 22 ± 1.1 years, with the majority (66.1%) aged 22-24. The gender distribution was 55.8% male and 44.2% female. A significant majority (93%) were aware of mindfulness activities, and 60% reported participating in them. There was a significant difference in mindfulness awareness and practice, as indicated by p-values. Additionally, 81% of students believed that mindfulness practices positively influenced their academic performance. A statistically significant relationship was identified between mindfulness practices and self-reported academic achievements (p-value=0.002). Common barriers to practice included lack of time (61.8%), lack of interest (14.7%), and skepticism about its effectiveness (10.3%).CONCLUSION: The study's findings suggest a positive correlation between mindfulness practices and self-reported academic achievement among undergraduate medical students. Most participants reported improvements in educational performance and mental health, highlighting the potential benefits of incorporating mindfulness practices into medical education.